Treatment planning system commissioning of the first clinical biology‐guided radiotherapy machine. Issue 8 (29th May 2022) - Simiele, Eric; Capaldi, Dante; Breitkreutz, Dylan; Han, Bin; Yeung, Timothy; White, John; Zaks, Daniel; Owens, Michael; Maganti, Srinath; Xing, Lei; Surucu, Murat; Kovalchuk, Nataliya
Abstract: Purpose: The RefleXion X1 is a novel radiotherapy machine designed for image‐guided radiotherapy (IGRT) and biology‐guided radiotherapy (BgRT). Its treatment planning system (TPS) generates IMRT and SBRT plans for a 6MV‐FFF beam delivered axially via 50 firing positions with the couch advancing every 2.1 mm. The purpose of this work is to report the TPS commissioning results for the first clinical installation of RefleXion™ X1. Methods: CT images of multiple phantoms were imported into the RefleXion TPS to evaluate the accuracy of data transfer, anatomical modeling, plan evaluation, and dose calculation. Comparisons were made between the X1, Eclipse™, and MIM™. Dosimetric parameters for open static fields were evaluated in water and heterogeneous slab phantoms. Representative clinical IMRT and SBRT cases were planned and verified with ion chamber, film, and ArcCHECK @ measurements. The agreement between TPS and measurements for various clinical plans was evaluated using Gamma analysis with a criterion of 3%/2 mm for ArcCHECK @ and film. End‐to‐end (E2E) testing was performed using anthropomorphic head and lung phantoms. Results: The average difference between the TPS‐reported and known HU values was −1.4 ± 6.0 HU. For static fields, the agreements between the TPS‐calculated and measured PDD10, crossline profiles, and inline profiles (FWHM) were within 1.5%, 1.3%, and 0.5 mm, respectively. Measured output factors agreed with the TPS within 1.3%. Measured and calculated dose for static fields in heterogeneous phantoms agreed within 2.5%. The ArcCHECK @ mean absolute Gamma passing rate was 96.4% ± 3.4% for TG 119 and TG 244 plans and 97.8% ± 3.6% for the 21 clinical plans. E2E film analysis showed 0.8 mm total targeting error for isocentric and 1.1 mm for off‐axis treatments. Conclusions: The TPS commissioning results of the RefleXion X1 TPS were within the tolerances specified by AAPM TG 53, MPPG 5.a, TG 119, and TG 148. A subset of the commissioning tests has been identified as baseline data for an ongoing QA program.